2013
DOI: 10.1186/1471-2318-13-113
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Cockcroft-Gault, MDRD, and CKD-EPI in estimating prevalence of renal function and predicting survival in the oldest old

Abstract: BackgroundThe question for prevalence estimation and validation of the various eGFRs in old age is still under debate. To assess renal function with increasing age, we estimated mean eGFR, in subjects aged 20–85 years. Furthermore, we assessed prevalence of eGFR in a population-based sample of 85 year olds and investigated the performance of these eGFRs in predicting mortality in the oldest old.MethodsRenal function with increasing age was assessed in subjects aged 20–85 years from the Bronovo Study Cohort. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 23 publications
1
21
0
6
Order By: Relevance
“…The C-G method was associated with lower eGFR computations. The authors also found that the CKD-EPI eGFR closely approximated the gold-standard [15,16]. In their study, Matsushita et al found that CKD-EPI, which out-performs MDRD, led to the reclassification of many patients from lower to higher renal function categories [17].…”
Section: Michel Et Al and Willems Et Al Compared The Egfr Computed mentioning
confidence: 85%
“…The C-G method was associated with lower eGFR computations. The authors also found that the CKD-EPI eGFR closely approximated the gold-standard [15,16]. In their study, Matsushita et al found that CKD-EPI, which out-performs MDRD, led to the reclassification of many patients from lower to higher renal function categories [17].…”
Section: Michel Et Al and Willems Et Al Compared The Egfr Computed mentioning
confidence: 85%
“…Although the CG formula is widely used, it is not well validated for elderly patients. It is reported that this formula tends to give relatively lower eGFRs for patients older than 70 years [19]. Median (range) eGFR for the younger and older patients was 60.9 (12.5-120.5) and 44.1 (14.8-85.2) ml/min/1.73 m 2 , respectively.…”
Section: Discussionmentioning
confidence: 95%
“…However, Carter et al showed scarce differences between the CKD‐EPI and MDRD equations, and among the elderly patients, CKD‐EPI equation increased CKD prevalence . Another study focusing on the effect of age, the Cockcroft‐Gault equation, estimated lower eGFRs, and Cockcroft‐Gault and MDRD equations predicted mortality, but not CKD‐EPI …”
Section: Discussionmentioning
confidence: 99%